Animalistic Images in Prose by E. Canetti and А. P. Platonov - E. M. Shastina; N. E. Seybel (Научный диалог, 2017)
Animalistic images in the prose of the Austrian writer, Nobel prize winner Elias Canetti (1905-1994) and the Russian writer A. P. Platonov (1899-1951) are discussed. Prose works of Canetti and Platonov belonging to different genres (notes, novel, story, essay) were compared. The authors use the term animalistic context , as in the works of Canetti and Platonov there are different types of representation of relations “man - animal,” various manifestations of animism, from mythological images of animals to “the mixing of sentient beings,” when the boundaries between man and animal are erased, which allows to make a conclusion about special anthropomorphic and zoomorphic perception of animals that characterizes both authors. The question about specificity of functioning of the animal images included in “animal context” of Canetti and Platonov is raised. Special attention in the description of the animal images is paid to the characteristics of progressive and regressive metamorphosis occurring with humans and animals. It is proved that the research of the work of Canetti and Platonov taking into account “animal context” seems relevant to detecting common patterns of development of European literature and culture of the first third of the 20th century.